The factors that lead to the wages differential: a case study in Yoke Food Industries Sdn. Bhd / Nor Aina Arsad and Nurulashikin Abdul Shamit - Arsad, Nor Aina; Abdul Shamit, Nurulashikin (2010)
The purpose of this research is to determine which factors that leads to the wages differential at Yoke Food Industries Sdn. Bhd, Senai, Johor. The objective of this research is to investigate the relationship between independent variables which are demographic factors (education, work experience, occupational segregation based on gender) that will influence the dependant variable which is wages differential in Yoke Food Industries Sdn. Bhd. The population of this research is about 216 employees in the Yoke Food Industries Sdn. Bhd. The sample size for this research is 140 employees that will be representative for the whole population. In this study, proportionate stratified random sampling technique will use to select the sample from five departments in Yoke Food Industries Sdn. Bhd. The researchers use Descriptive Statistic, Pearson Correlation, Multiple Regressions and Cronbach’s Alpha in order to analyze the data gathered by using Statistical Package for Social Sciences (SPSS) version 16.0. The result will give benefit to the employees and also the employer.